2011
DOI: 10.1007/s10753-011-9407-4
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress, P66shc, and P-Akt/Akt Mediate Adjuvant-Induced Inflammation, Which Is Blunted by Argirein, a Supermolecule and Rhein in Rats

Abstract: We investigated the anti-inflammatory activities of argirein and rhein on inflammatory edema in rat paw which was caused by complete adjuvant, compared with ibuprofen. We hypothesized that the adjuvant-induced inflammation is attributed to upregulation of activating transcript factor 6 (ATF6; a chaperone for endoplasmic reticulum (ER) stress), p66Shc (an adaptive protein modulating oxidative stress), and NADPH oxidase subunits p22phox and gp91phox in the inflamed tissues. Biomarkers were measured in the rat pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 46 publications
6
38
0
Order By: Relevance
“…In the primary evaluation of severity of CP, less inflammatory infiltrates were observed in the pancreatic tissues of CP mice that were prophylactically and therapeutically fed with rhein; meanwhile, the cerulein-elevated systemic pro-inflammatory cytokines namely TNF-α and IL-1β were accordingly reduced in those rhein-treated animals. Our results here are in agreement to the findings of other research groups that the anthraquinone compound exerts pharmacological activities against inflammatory diseases majorly inhibiting the production of TNF-α and IL-1β and hence resulted in a suppressed recruitment of immune cells [31,43]. In terms of pancreatic architecture, the degree of atrophy was significantly attenuated in those rhein-treated CP mice as implicated by the substantial restoration of their pancreatic wet weights.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the primary evaluation of severity of CP, less inflammatory infiltrates were observed in the pancreatic tissues of CP mice that were prophylactically and therapeutically fed with rhein; meanwhile, the cerulein-elevated systemic pro-inflammatory cytokines namely TNF-α and IL-1β were accordingly reduced in those rhein-treated animals. Our results here are in agreement to the findings of other research groups that the anthraquinone compound exerts pharmacological activities against inflammatory diseases majorly inhibiting the production of TNF-α and IL-1β and hence resulted in a suppressed recruitment of immune cells [31,43]. In terms of pancreatic architecture, the degree of atrophy was significantly attenuated in those rhein-treated CP mice as implicated by the substantial restoration of their pancreatic wet weights.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, rhein, the active metabolite of acetylrhein, is the predominant form found in bloodstream that possesses potent bioactivities in mammals including rodents, rabbits and human [39]. The pharmacological actions of this anthraquinone derivative have been lately evidenced in various inflammatory diseases such as arthritis [31,40] and dermatological disorders [41]. A recent study by He et al demonstrated that rhein could effectively inhibit the activation of renal interstitial fibroblasts in mice [35] implicating its potential in targeting fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…l ‐arginine alone had no definite benefit in relieving acute inflammation and biomarkers in rat paw oedema, in comparison with either rhein or argirein; argirein was more prominent in suppressing the inflammatory oedema than rhein at 1 h. Rhein released from argirein acts as an active metabolite, suppressing inflammatory responses, and the content of rhein in argirein, calculated based on weight to weight ratio, is about 65% compared with unchanged rhein. The efficacy of argirein encountering inflammatory reactions is at least the same as rhein, as found in the present study and in studies of adjuvant arthritis in rats [32] . Based on these findings, we may conclude that this is because of synergistic action of l ‐arginine with rhein in improving vascular endothelium in the inflamed regions, beneficial to anti‐inflammatory activity of argirein.…”
Section: Discussionsupporting
confidence: 87%
“…The inflammatory edema was accompanied by upregulation of cytokines [51]. The spontaneous production of IL-1 by rheumatoid synoviocytes can be inhibited by anti-TNF antibodies, suggesting that the activity of TNF occurs earlier in the cascade than that of IL-1, whereas IL-6 occupies a position later in the cascade being produced in response to either TNF or IL-1 [52].…”
Section: Discussionmentioning
confidence: 99%